Stretching lattice models of protein folding - Socci, Nicholas D. (The National Academy of Sciences, 1999)
A new class of experiments that probe folding of individual protein domains uses mechanical stretching to cause the transition. We show how stretching forces can be incorporated in lattice models of folding. For fast folding proteins, the analysis suggests a complex relation between the force dependence and the reaction coordinate for folding.